PENGARUH MUJA MATCAH BERBANTUAN METODE PROBLEM BASED LEARNING TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA : SEBUAH STUDI EKSPERIMENTAL - Siti Sholikah; Ida Putri Rarasati; Adin Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problems raised are the lack of understanding and interest of students in fraction material and the limited use of technology-based learning media, which results in learning outcomes below the KKM. This study aims to explain the effect of Muja Matcah assisted by the problem-based learning method on interest and learning outcomes in mathematics partially and simultaneously. This study uses a quantitative approach with a quasi-experimental design in the form of a pretest-posttest non-equivalent control group. The subjects of the study involved 50 students, consisting of 25 students in class IV A and 25 students in class IV B at SD Negeri Kanigoro 03. Data analysis used the T test to see the effect partially and the MANOVA test to see the effect simultaneously. The results of the T test showed that Muja Matcah had a significant effect on learning interest tcount 2.236> ttable 2.069, Sig. 0.035 < 0.05 and learning outcomes tcount 2.429 > ttable 2.069, Sig. 0.023 < 0.05. MANOVA test shows a significant effect on interest and learning outcomes, fcount interest 15.593 > ftable 4.26 and fcount results 53.721 > ftable 4.26. In conclusion, Muja Matcah assisted by problem based learning method has a significant effect on interest and mathematics learning outcomes of fourth grade students of SD Negeri Kanigoro 03, both partially and simultaneously.